Educational Adequacies of Kindergartens' Teachers and its Relationship with Culturing Child of Kindergarten with Life Environmental Skills - Fieldwork Study - انوار فاضل الشوك ليلى نجم ثجيل (College of Education for Women, 2019)
The current research includes several axes, which determine the basic professional skills among kindergarten teachers and government civil Balraudhat and their relationship to educate kindergarten children with life skills teacher Albaiah.boattabar his career. And this profession imposes upon that possesses special skills, qualify him to do his roles. The teacher experimenter, researcher and owner of philosophy and organizer and director of the positions and educational director of the interactions of classroom and non-classroom. And educational systems that are responsible for the preparation of the emerging needs constant review in order to improve internal Kvaiadtha select the best input consistent with the reality of education, so as to meet the regulations outputs, movement-based competencies relatively valid for all stages and subjects, is an active movement to make teachers' positive and effective in influencing more on their students, and that a return to the great role and it is important inside. It is an educational institution here comes the need to raise teacher competences and basic axis another educate kindergarten children with life skills and environmental as one of the basic skills of any individual to satisfy his needs in order to continue to stay .oayda for the continued progress and development experience the methods life, especially in light of the times we live in an era Amwalimomatah and technological revolution, as we Noajo many of the most important challenges of building a generation capable of innovation to keep pace with the challenges of this era and witnessing innovations and successive changes, Jill Gard to cope with life and the problems of society. So has the skills of researchers will select life skills that you think are so important for children at this age and during this time period, which hails rapid progress in information technology and operations, a quick connect environmental skills.  The importance of research and the need for him o proceed from being dealt with professional features for kindergarten teachers because of these characteristics of importance in building the characters suffer so far from the lack ofinterest, therefore, to identify these characteristics help in the planning process for the preparation of the teacher and the training also helps in the selection of parameter specifications suitable to work at this stage misfortune extremely important, a kindergarten o may draw the attention of parents to determine the level of the child's abilities at this stage and to cooperate with the parameters to improve the quality of their children's abilities by identifying the competencies required. o The importance of addressing environmental skills make the child is able to manage the health interaction between him and the others and with the environment and society around him. o The child's success in life depends on what attributes of the different skills.  research goals  identify the educational skills among kindergarten teachers  recognize the difference in the level of educational skills among kindergarten teachers depending on the variable academic achievement.  Identify the kindergarten child life skills and environmental culture  Identify the relationship between educational competencies for teachers of kindergarten and life skills of kindergarten children.  The research sample  The research sample included on (78) a parameter in (16) Kindergarten (8) kindergartens government (8) civil kindergartens and 10% of government and private kindergartens to the city of Baghdad / Karkh and according to statistics from the Ministry of Education for 2015. While the research sample included Children Riyadh phases (kindergarten and primer) (200) boy and girl a random sample of the Directorate of Education Baghdad / Karkh / for the academic year 2014-2015  search tools  To achieve the goals of research has been building measure includes (31) is represented Alkqayat educational and applied to the sample parameters kindergarten. As has been the adoption of life skills and environmental measure it has been confirmed validity and reliability of the two scales  Statistics  All processors statistical adopted in the reliability and validity of the scale and analyze the results on the program (spss, 1996)  Results  After study and analysis was reached following results  The educational skills for kindergarten teachers is weak and this Aukd parameters urgent need for all proposed educational competencies.  The second objective refers to the absence of a difference in the educational competencies depending on the attainment  The third goal shows that kindergarten children are not being life skills and environmental  The fourth goal third shows the weak relationship between owning a kindergarten child life skills and environmental Enjoy kindergarten teachers educational competencies.  Recommendations and proposals  Search resulted in numerous recommendations and proposals, including - :  holding intensive training courses for kindergarten teachers in the areas of teaching methods and methods of treatment of children and guide their behavior .ozlk to enrich their ideas with examples and exercises and educational applications simple and excitingand equip them with the necessary tools and training for all equipment and work on the preparation before doing it  The need to intensify supervision on the process of kindergarten teachers and providing them with everything new in the field of specialization, using the method of exchange of visits and the presence of typical lessons constantly of the importance of this in the nature of the learning acquired.